Strategi Manajemen Sumber Daya Manusia Berbasis Syariah pada UMKM Batik Madura - Akh. Fawaid; Holis, Moh; Sayyidi Sayyidi (Journal of Economic and Islamic Research, 2025)
This study aims to analyze the sharia-based human resource (HR) management strategy in batik Micro, Small, and Medium Enterprises (MSMEs) in Pamekasan Regency. Batik MSMEs are one of the leading sectors in the region that not only contribute to the local economy but also preserve Madurese cultural heritage. In HR management, there are still many MSME actors who have not implemented a structured management system, even though the integration of sharia values ??can be a solution to create a productive and ethical work climate. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation on several batik MSME actors. The results of the study indicate that values ??such as honesty (?idq), amanah, justice, and deliberation have begun to be implemented, although they have not been fully integrated into the HR management system. The main inhibiting factors are limited understanding and the absence of practical guidelines on sharia-based HR management. Therefore, this study recommends the need for managerial and spiritual training for batik MSME actors to support more Islamic and professional HR management.